Concept Of Outpatient Urology Development In The Process Of Restructuring Using The Experience Of Public-Private Partnership According To Scientific Publications (Journal of Pharmaceutical Negative Results, 2023)
Over the past decades, diseases of the genitourinary system have been firmly holding the third position in the list of diseases in the Russian Federation. In the structure of primary disability, diseases of the genitourinary system occupy about 4%. In comparison, the indicators of complete rehabilitation of disabled people in this group are 1.2–2%, which is 2.5–3 times lower than most other diseases.The costs of outpatient care, compared with 2016, will be reduced by 1.6 times - from 113.4 to 68.9 billion rubles in 2022. In such conditions, it is necessary to intensify the measures taken to attract private capital using public-private partnership (PPP) mechanisms to develop and modernize the healthcare infrastructure and, as a result, improve the quality of medical care.